Marketing decisions as an intermediary variable of the nature of the relationship between Environmental Turbulence and marketing effectiveness exploratory study of Carrefour branches in Erbil Governorate - حامد, محمد محمود (Journal of Economics and Administrative Sciences, 2025)
The organizations, represented by its Management, are working hard in various ways to identify the environmental disturbances that occur in their environment and to investigate and follow up the movement of these disturbances and to respond to them through the decisions they make in an attempt to keep pace with the work and sustainability of their activities, including those decisions, marketing decisions taken by the environmental disturbulence in the market of the organization, the inability of these organizations to read the indicators of these disturbulence correctly displays their marketing effectiveness to vibration and decline in the negative.The current research is based on a fundamental problem that environmental disturbances affect the marketing effectiveness of the organization through marketing decisions. Therefore, the importance of research in both theoretical and field aspects is important in highlighting these dimensions. The objective of the current research is to provide a practical study of the field  and The relationship between these dimensions.In order to achieve the objectives of the research, a questionnaire was designed to include (30) items to collect the initial data from the research sample which consist of (175) individuals of the respondents who are in the branches of Carrefour in the province of Arbil. In the light of  collected and data analyzed the hypotheses were tested. The researcher used a number of statistical and descriptive methods (Frequency and percentage, computational, standard deviations, sensitivity and efficiency testing, simple correlation coefficient and path analysis) and by using the Statistical Package of Social Sciences (SPSS). The researcher reached a number of conclusions, which was that the changes that result from the environmental disturbances, it is imperative for organizations to adapt to those changes in order to maintain the level of performance of the Organization, including the organization investigated taking into account the marketing decisions taken by these disorders which will be reflected in the marketing effectiveness of the organization.